Enhancing Tourist Experiences in Glodok Pancoran Through Virtual Tours - Christina, Angelica; Tony, Tony; Handhayani, Teny (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
This research aims to develop a web-based tourist destination application for Glodok Pancoran, Jakarta, to improve tourist experience and promote local culture and culinary. The methods used in developing this application include database design, development using Visual Studio Code, React for the frontend, and Go (Golang) for the backend, as well as database management with MySQL. The app was tested using black box method and System Usability Scale (SUS) assessment to ensure functionality and user satisfaction. With an Agile approach, the app integrates Google Maps and Street View to provide virtual tours, which is a new innovation in promoting local tourism. The results showed a high level of user satisfaction with an average SUS score of 90.33, which was categorized as excellent. This study highlights the importance of virtual tours in tourism, especially for first-time visitors, and recommends further development based on user feedback to improve tourism and the local economy.